The conqueror [videorecording (DVD)] - Powell, Dick, 1904-1963; Wayne, John, 1907-1979; Hayward, Susan, 1917-1975; Armendáriz, Pedro, 1912-1963; Moorehead, Agnes, 1900-1974 (GoodTimes Home Video Corp., 1999)
In 12th century China, Genghis Khan falls in love with the daughter of his enemy.